Applications of Hamiltonian and Laplace Transform in an Economic Growth Model - Liutang Gong (Acta Mathematica Scientia, 2000)
This paper analyzes the long-run effects and short-run effects of foreign aid on the domestic economy by using the Hamilton system and Laplace transform. It is found that an increase in the foreign aid has no long-run effect on the foreign borrowing, domestic capital accumulation and the foreign direct investment in the home country, but increases the steady-state consumption level the same amount. However, the short-run analysis presents that increasing foreign aid does not affect the initial consumption level and the initial consumption increase rate; but it affects the initial savings positively.